PENGARUH RASIO KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS PERUSAHAAN OTOMOTIF - WAHYU WIDARJO; DODDY SETIAWAN (Jurnal Bisnis dan Akuntansi, 2009)
Financial distress is phase of degradation of condition of company's finance that happened before the happening of bankruptcy or liquidation. Financial distress condition happens before bankruptcy. This condition can be predicted using models that have developed by many researchers. The purpose of this research is to examine financial ratios that affect financial distress on automotive industries. The sample of this research consists of 49 non distress firms and 6 distress firms, it is chosen by purposive sampling. The statistic method which is used to test on the research hipotesis is logistic regression. The result of this research shows that liquidity ratio (current asset-inventory/ current liabilities) and profitability ratio (net income/total asset) affect financial distress.